Analisis Pengaruh Literasi Keuangan, Pencatatan Keuangan, dan Pemanfaatan Teknologi Digital terhadap Perilaku Keuangan Individu: Analysis of the Influence of Financial Literacy, Financial Record-Keeping, and Utilization of Digital Technology on Individual Financial Behavior - Nabila Oktaviansyah; Amanda Salsabila; Saqilla Nur Alaida; Zahra Marsya Qilla; Kayla Aura Fatma; Rudianto Rudianto (CV Warnak Johanna Nusantara, 2026)
The development of digital technology and the rise of financial services have changed the way people, especially the younger generation manage their finances. However, this convenience is not commensurate with financial literacy and financial recording. The purpose of this study is to examine the extent to which financial literacy, financial record-keeping, and the use of digital technology affect individual financial behavior, especially in students who have incomes. In this study, the author used a quantitative approach by distributing questionnaires to respondents. Data were analyzed using a multiple linear regression approach through IBM SPSS Statistics 26 software, which included hypothesis testing (t-test and F-test), classical assumption testing, and data quality testing. That the significance value of financial literacy based on the t-test was obtained by tcal > ttable (2.063 > 1.985), thus Ho1 was rejected. The significance value of financial recording based on the t-test was obtained by tcal > ttable (2.108 > 1.985), thus Ha2 was accepted. The significance value of the use of digital technology based on the t-test was obtained by tcal > ttable (2.605 > 1.985), thus Ho3 was rejected. In addition, the results of the simultaneous analysis show that the combination of cognitive, behavioral, and technological aspects can strengthen an individual's ability to make financial decisions.